The Role of Teachers in Creating an Inclusive Learning Environment in Elementary Schools - Kadek Hengki Primayana; Bunga Yani; Putu Ardelia Giovanni Wirama; Gede Wendi Yudiartha; Gede Sukadana; Gede Ambara Kusuma Wardana (Indonesian Journal Publisher, 2026)
This study aims to determine the role of teachers in creating an inclusive learning environment in elementary schools. The study used a literature review method by analyzing various journals and scientific articles related to inclusive education. The results indicate that teachers play a crucial role in creating a learning environment that embraces student diversity, provides equitable learning, and fosters positive social interactions in the classroom. Teachers are also required to possess social and pedagogical competencies and the ability to adapt to student needs. However, several challenges remain, such as a lack of understanding of inclusive education and limited school facilities. Therefore, training and support from various parties are needed to ensure the success of inclusive learning